Effects of dietary energy level and intake of corn by-product-based diets on newly received growing cattle: antibody production, acute phase protein response, stress, and immunocompetency of healthy and morbid animals. (19th February 2018) - Spore, Tyler J; Montgomery, Sean P; Titgemeyer, Evan C; Hanzlicek, Gregg A; Vahl, Chris I; Nagaraja, Tiruvoor G; Cavalli, Kevin T; Hollenbeck, William R; Wahl, Ross A; Blasi, Dale A
Abstract: Effects of dietary energy level and intake of corn by-product-based diets on antibody production, acute phase protein response, stress, and immunocompetency of healthy and morbid newly received growing cattle were evaluated. Four dietary treatments were formulated to supply 0.99, 1.10, 1.21, and 1.32 Mcal NEg / kg DM and were offered at 100%, 95%, 90%, and 85% of ad libitum based on 0.99/100 treatment intake, respectively. Thirty-two pens were utilized with approximately 12 animals/pen. Four animals from each pen (32/dietary treatment) were randomly selected and used to serve as a subset to monitor immune function and acute phase proteins following a split-plot design. In addition, two animals were randomly and independently selected from each pen (16/dietary treatment) and used to measure fecal cortisol metabolite. Additionally, animals removed from the pen one (M1), two (M2), or three (M3) times and classified as morbid were bled in conjunction with a healthy control (H) removed at the same time and the serum analyzed for the same parameters. A quadratic response to time ( P < 0.01) was detected for haptoglobin concentrations and for antibody titers for bovine viral diarrhea type 1 (BVD-I) and infectious bovine rhinotracheitis (IBR ; P < 0.01). Haptoglobin was lowest on arrival, highest on day 14, and similar to baseline levels by day 27. Titer levels for BVD-I and IBR were lowest on arrival, higher on day 14, and significantly higher on day 27. Titers for bovine viral diarrhea type 2 (BVD-II) responded linearly ( P < 0.05) with lower levels on arrival and highest levels on day 27. Haptoglobin was elevated in morbid animals compared to healthy pen mates ( P < 0.05). Titer levels for BVD-I and IBR were also higher in healthy animals compared to animals pulled for morbidity ( P < 0.01). Fecal cortisol was higher on arrival than on day 14 ( P < 0.05). Dietary treatment had no effect on any of the parameters investigated. In summary, high-energy receiving diets based on fermentable fiber from by-products can be fed to newly received growing cattle without negative effects on antibody production toward vaccines, inflammation, or overall stress. In addition, haptoglobin concentrations and titer levels for BVD-I and IBR viruses are higher in healthy animals compared to sick animals.